A study to determine the association between pattern of calcification in ct scan and staging of retinoblastoma in Hospital University Science Malaysia (HUSM). - Goon, Rozita (2011)
Introduction: Retinoblastoma is one of the most common intraocular malignancy in children under 15 years old. About 80% of cases occurs in patients under 3 years old. The incidence varies form countries to countries. In United States of America, it occurs in 1 of every 15000 live birth. Most incidence of retinoblastoma is unilateral, bilateral involvement is seen in approximately 30% of cases and it is detected earlier. Physical and radiological examination helps in diagnosing retinoblastoma. CT scan of the orbit is one of the important tools in diagnosing retinoblastoma. Intraocular calcification can be detected in about 80% of the CT scan of orbit. Many researches have been performed since 1980s to determine association between intraocular calcification in retinoblastoma with prognosis and size of the tumour. Objectives: To determine frequency of intraocular calcification in retinoblastoma and association between the pattern of calcification with histopathological examination, clinical data and staging. Patients and methods: This was a retrospective descriptive study. All patients had undergone pretreatment CT scan of the orbit and enucleation. Characteristic of calcification on CT scan images which were presence of calcification, size, site and Hounsfield Unit of calcification were recorded. CT scan images were reviewed via GE Centricity PACS- IW (Intregrated web) version 3.71. Histological findings which were presence of calcification, size, site of tumour and optic nerve involvement were recorded. History of presenting illness, family history, demographic data and clinical classification were sought form medical record and recorded. Association between characteristic of calcification and histological findings, clinical data and staging were determined. Results: There was 95% intraocular CT calcification seen in retinoblastoma in this study. There was significant association between presence of calcification on CT and presence of calcification on HPE(p=0.042). There was also significant association between presence of HPE calcification and CT calcification site(p=0.016). Significant association noted between CT calcification size and strabismus(p=0.035). However. there was no significant association between the patterns of calcification on CT with staging of retinoblastoma. Conclusion: Although presence of calcification on CT scan was used as a criteria to diagnosed retinoblastoma, there is no significant association between patterns of the calcification with staging in retinoblastoma.